2021
DOI: 10.3389/fphar.2021.728015
|View full text |Cite
|
Sign up to set email alerts
|

Tristetraprolin Gene Single-Nucleotide Polymorphisms and mRNA Level in Patients With Rheumatoid Arthritis

Abstract: To observe and evaluate the correlation between single-nucleotide polymorphisms (SNPs) and messenger RNA (mRNA) level related to tristetraprolin (TTP) in Chinese rheumatoid arthritis (RA). TapMan SNP was used for genotyping analysis in 580 RA patients and 554 healthy people. Association between TTP gene polymorphisms (rs251864 and rs3746083) and RA was obtained. Quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR) technology was applied for the detection of TTP mRNA level in periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Given its ability to target and reduce the mRNA levels of several in ammatory cytokines, including TNF-a, it is generally considered to play a crucial function in the development of RA pathology (31). This nding is supported by the research of Yang et al (32), whose study reported decreased levels of TTP mRNA in PBMCs collected from patients with RA. Additionally, the authors identi ed an association between a SNP (rs3746083) located in the gene encoding for TTP and RA susceptibility in Chinese RA patients.…”
Section: Discussionmentioning
confidence: 91%
“…Given its ability to target and reduce the mRNA levels of several in ammatory cytokines, including TNF-a, it is generally considered to play a crucial function in the development of RA pathology (31). This nding is supported by the research of Yang et al (32), whose study reported decreased levels of TTP mRNA in PBMCs collected from patients with RA. Additionally, the authors identi ed an association between a SNP (rs3746083) located in the gene encoding for TTP and RA susceptibility in Chinese RA patients.…”
Section: Discussionmentioning
confidence: 91%
“…A recent study by Yang et al [14] was "the first study to prove that TTP dysregulation might be related to the pathogenesis and development of Rheumatoid arthritis (RA), and the polymorphism of the TTP gene may be protective of RA in a Chinese population. They suggested that TTP might be involved in the regulation of autoimmune diseases".…”
Section: Discussionmentioning
confidence: 99%
“…ICAM-1 (along with VCAM-1) is involved in multiple mechanisms that promote inflammation, predominantly by promoting local infiltration of inflammatory cells (Klimiuk et al, 2002). Supporting the relevance of TTP in RA, Yang et al reported a reduction of TTP mRNA in human PBMCs purified from RA patients and an association between a SNP located in the gene encoding for TTP (rs3746083) and RA predisposition in Chinese RA patients (Yang et al, 2021).…”
Section: Rbps and Rheumatoid Arthritismentioning
confidence: 99%